Parasite destroys mango pest - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
A new species of mealybug which was causing millions of dollars' worth of damage to mango and other trees in West Africa is being successfully counteracted by an Asian parasite. Since 1981 mangoes, mandarins, guavas, breadfruit, and citrus have...